PENGARUH KONSERVATISME AKUNTANSI DAN DEBT MATURITY TERHADAP EFISIENSI INVESTASI - FRANSISKA, EMILIA; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2018)
The decline in mining commodity prices from 2012 until 2016 has made mining companies run into difficult time. This makes the company make an effort to survive. The efforts made are investment efficiency. This phenomenon is leading to need for a research related to any factors that could affect investment efficiency. This study goals to determine the effect of conservatism and debt maturity on invesment efficiency in mining companies listed on the Indonesian Stock Exchange in 2012-2016. This research used quantitative method with purposive sampling. The total sample of study are 36 companies so the amount of data are 180. The result this studi indicate that conservatism and debt maturity have no effect on investment efficiency.Keywords : Investment Efficiency, Conservatism, Debt Maturity